A Dual‐Modal Magnetic Resonance/Photoacoustic Imaging Tracer for Long‐Term High‐Precision Tracking and Facilitating Repair of Peripheral Nerve Injuries. Issue 13 (31st March 2022) - Ren, Jingyan; Tang, Xiaoduo; Wang, Tao; Wei, Xin; Zhang, Junhu; Lu, Laijin; Liu, Yang; Yang, Bai
Abstract: Neuroanatomical tracing is considered a crucial technique to assess the axonal regeneration level after injury, but traditional tracers do not meet the needs of in vivo neural tracing in deep tissues. Magnetic resonance (MR) and photoacoustic (PA) imaging have high spatial resolution, great penetration depth, and rich contrast. Fe3 O4 nanoparticles may work well as a dual‐modal diagnosis probe for neural tracers, with the potential to improve nerve regeneration. The present study combines antegrade neural tracing imaging therapy for the peripheral nervous system. Fe3 O4 @COOH nanoparticles are successfully conjugated with biotinylated dextran amine (BDA) to produce antegrade nano‐neural tracers, which are encapsulated by microfluidic droplets to control leakage and allow sustained, slow release. They have many notable advantages over traditional tracers, including dual‐modal real‐time MR/PA imaging in vivo, long‐duration release effect, and limitation of uncontrolled leakage. These multifunctional anterograde neural tracers have potential neurotherapeutic function, are reliable and may be used as a new platform for peripheral nerve injury imaging and treatment integration. Abstract : A novel multifunctional nano‐neural tracer (microspheres‐Fe3 O4 @COOH‐BDA) combining antegrade neural tracing imaging and therapeutic properties for the peripheral nervous system. The tracer has many notable advantages over traditional versions, including dual‐modal magnetic resonance/photoacoustic (MR/PA) imaging in vivo, long‐term release effect, and potential neurotherapeutic function.